IDENTIFICATION OF ECONOMIC AND DEMOGRAPHIC FACTORS TO WASTE GENERATION IN CITIES OF ECONOMIC CORIDOR IN JAVA AND SUMATERA - PRAJATI (NIM : 25312001), GITA
Population growth, urbanization and economic growth, resulting an increase of municipal solid waste. The purposes of this study were to identify patterns associated local waste development in Java and Sumatra, to analyze the relationship between economic and demographic variable to waste generation and to do the projection of waste generation using test models. Cluster, quadrant and Klassen typology analysis was done to determine the pattern of characteristics and waste generation in Java and Sumatra. Then analyzed the relationship between economic and demographic variables against waste generation and also performed Daskalopoulus, kahjuria and development of Khajuria model test. Based on cluster, quadrant and klassen typology analysis, there are three patterns of waste generation in Java and Sumatera. Population, consumer price index and GDP indicate the amount of waste generations. The test result of Daskalopoulos model was waste generation in Java and Sumatra can be explained 33.7% by consumption expenditure per category. The test result of Khajuria model was waste generation in Java and Sumatra can be explained 42.5% by total population, GDP, and school’s period. The development of Khajuria model showed that waste generation in Java and Sumatra can be explained 65.6% by total population, GDP, school’s period, literacy, economic growth and population density. Waste generations projected by the development of Khajuria model. Waste generation’s projection showed that Tanjungpinang and Pangkalpinang are cities with the highest waste generation in per five years. The cost that is spent for waste management also bigger in these city, above 0.8% from the GDP.